An active attitude and the spirit of doing. Hands-on work and results at the Information Technology department of Oulu UAS - Nousiainen, Eero; Peltola, Anne; Ilmakangas, Virpi; Rontu, Riitta (Oulun ammattikorkeakoulu, 2014)
Oulu UAS educates professionals for the needs of Northern Finland, whose competence corresponds to the needs and development of working life in the region. We react quickly to the changes occurring in working life and the requirements of new competence. At the degree programme of Information Technology we aim to develop our teaching to include more real-life project work: our curricula include increasingly more company-related projects. This way we are able to provide our students with a more realistic view of the everyday work at companies, and also improve their employment opportunities. The purpose of this publication is to spread the word about the projects and results achieved by the students and staff of the Information Technology department. In addition to student projects, our department is also involved in many domestic and international projects well worth mentioning. Yearly, our students complete hundreds of thesis and project work. This publication also presents good examples of our successful projects.